Effects of temperature on drying kinetics and biochemical composition of Caulerpa lentillifera - Fakhrulddin, I. M.; Ramaiya, S. D.; Muta Harah, Z.; Nur Leena Wong, W. S.; Awang, M. A.; Ismail, N. I. M. (Rynnye Lyan Resources, 2022)
Caulerpa lentillifera (phylum: Chlorophyta) is a seaweed that is widely consumed by local communities across Asia. The effects of different oven-dried temperatures on the drying kinetics and phytochemical constituents of C. lentillifera were studied. This kinetic study used three different thin-layer models, i.e., Lewis, Henderson and Pabis, and Logarithmic models. Among these, the Logarithmic model was the most suitable model that could be determined the seaweed drying behaviours (R-square > 0.9923, RMSE < 0.0004). Drying the C. lentillifera at 50oC resulted in a higher extraction yield (1.00%) with a significant concentration of total phenolic content and total flavonoid content at 1.027 mg GAE/g, and 59.655 mg RU/g, respectively.